Effect of Sodium Nitrite on Ischaemia and Reperfusion-Induced Arrhythmias in Anaesthetized Dogs: Is Protein S-Nitrosylation Involved? - Kovács, Mária (PLoS One, 2015)
BACKGROUND AND PURPOSE: To provide evidence for the protective role of inorganic nitrite against acute ischaemia and reperfusion-induced ventricular arrhythmias in a large animal model. EXPERIMENTAL APPROACH: Dogs, anaesthetized with chloralose and urethane, were administered intravenously with sodium nitrite (0.2 µmolkg(-1)min(-1)) in two protocols. In protocol 1 nitrite was infused 10 min prior to and during a 25 min occlusion of the left anterior descending (LAD) coronary artery (NaNO(2)-PO; n = 14), whereas in protocol 2 the infusion was started 10 min prior to reperfusion of the occluded vessel (NaNO(2)-PR; n = 12). Control dogs (n = 15) were infused with saline and subjected to the same period of ischaemia and reperfusion. Severities of ischaemia and ventricular arrhythmias, as well as changes in plasma nitrate/nitrite (NOx) levels in the coronary sinus blood, were assessed throughout the experiment. Myocardial superoxide and nitrotyrosine (NT) levels were determined during reperfusion. Changes in protein S-nitrosylation (SNO) and S-glutathionylation were also examined. KEY RESULTS: Compared with controls, sodium nitrite administered either pre-occlusion or pre-reperfusion markedly suppressed the number and severity of ventricular arrhythmias during occlusion and increased survival (0% vs. 50 and 92%) upon reperfusion. There were also significant decreases in superoxide and NT levels in the nitrite treated dogs. Compared with controls, increased SNO was found only in NaNO(2)-PR dogs, whereas S-glutathionylation occurred primarily in NaNO(2)-PO dogs. CONCLUSIONS: Intravenous infusion of nitrite profoundly reduced the severity of ventricular arrhythmias resulting from acute ischaemia and reperfusion in anaesthetized dogs. This effect, among several others, may result from an NO-mediated reduction in oxidative stress, perhaps through protein SNO and/or S-glutathionylation.